2018
DOI: 10.33844/mbr.2018.60288
|View full text |Cite
|
Sign up to set email alerts
|

Hotel Customer Loyalty: The Effect of Individual’s Similarity to Brand, Lifestyle Congruency and Cultural Brand Asset

Abstract: The main aim of this study was to investigate the factors affecting on customer loyalty of Mehr chain hotels in Yazd. Independent variables of this study included cultural brand asset, individual's similarity to brand, lifestyle congruency, intermediate variables of study included brand awareness, perceived quality, brand association, and customer satisfaction, and the dependent variable of study included brand loyalty. The population of this study included Iranian and non-Iranian quests of Mehr chain hotels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…Studies have shown that tourist motivation [10,11], perceived value [12,13] and destination attachment [14] affected their behavioural loyalty, while satisfaction [15,16], tourist destination identification [17,18], destination trust [19], destination image [20], customer participation [9,[21][22][23][24][25][26] and brand reputation [7,8,27] affected tourists' attitudinal loyalty. However, existing research on tourist loyalty principally focuses on hotels [28,29], leisure tourism [30], heritage tourism [31] and popular tourist destinations [32,33] rather than red tourism. The majority of articles on the latter centre on conception [34], the current situation [35], spatial distribution [36,37], planning, management and promotion [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that tourist motivation [10,11], perceived value [12,13] and destination attachment [14] affected their behavioural loyalty, while satisfaction [15,16], tourist destination identification [17,18], destination trust [19], destination image [20], customer participation [9,[21][22][23][24][25][26] and brand reputation [7,8,27] affected tourists' attitudinal loyalty. However, existing research on tourist loyalty principally focuses on hotels [28,29], leisure tourism [30], heritage tourism [31] and popular tourist destinations [32,33] rather than red tourism. The majority of articles on the latter centre on conception [34], the current situation [35], spatial distribution [36,37], planning, management and promotion [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%